2020
DOI: 10.1111/vcp.12864
|View full text |Cite
|
Sign up to set email alerts
|

Cytologic, histologic, microbiologic, and electron microscopic characterization of a canine Prototheca wickerhamii infection

Abstract: A 7-year-old, neutered male, mixed breed (Poodle-type) dog was presented to the internal medicine service at Affiliated Veterinary Specialists in Gainesville, Florida, for evaluation of a several week history of intermittent, dry coughing that was unresponsive to doxycycline or trimeprazine/prednisolone. A recent onset of bilateral mucoid nasal discharge was noted, and at the time of presentation, both nares were ulcerated and swollen (Figure 1). The dog had no reported travel history. Physical examination rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…In this study, both DAT+ and DAT- samples appeared hemolyzed, but the degree of hemolysis was higher in DAT+ samples, which may represent an artifact caused by in vitro lysis during shipment and storage (up to 5 days from collection). It is therefore not surprising to find discrepancies between Hb, PCV, and Hct values observed in the study reported here and in clinical practice [ 49 ]. When serum chemistry was available, we found hyperbilirubinemia more frequently in DAT+ dogs as expected in dogs with hemolytic anemia [ 46 ].…”
Section: Discussionmentioning
confidence: 64%
“…In this study, both DAT+ and DAT- samples appeared hemolyzed, but the degree of hemolysis was higher in DAT+ samples, which may represent an artifact caused by in vitro lysis during shipment and storage (up to 5 days from collection). It is therefore not surprising to find discrepancies between Hb, PCV, and Hct values observed in the study reported here and in clinical practice [ 49 ]. When serum chemistry was available, we found hyperbilirubinemia more frequently in DAT+ dogs as expected in dogs with hemolytic anemia [ 46 ].…”
Section: Discussionmentioning
confidence: 64%
“…In the histopathological examination, characteristic morula forms are helpful for diagnosing protothecosis, but there can be a lack of such findings due to the period of their life cycle. The external capsule of Prototheca species and the wall of yeasts stain positive with Grocott’s methenamine silver and periodic acid-Schiff stains [ 15 ]. Thus, they may be mistaken for Candida or Cryptococcus species, as we experienced.…”
Section: Discussionmentioning
confidence: 99%